Reproductive phenology of Ananas comosus var. erectifolius (L. B. Smith) Coppens & F. Leal. and its correlation with average temperature and rainfall (Research, Society and Development, 2021)
The species Ananas comosus var. erectifolius, known as curauá, belongs to the family of Bromeliaceae, in the Amazon region its foliage has benefits in the production of fibers and is also considered a medicinal species. Despite its importance, research on the behavior of phenology of species with great economic potential in the Amazon is scarce. The objective of this work was to study the reproductive phenophases of Ananas comosus var. erectifolius belonging to the Active Germplasm Bank of Embrapa Amazônia Oriental correlating with air temperature and rainfall, in order to indicate the most suitable time for the collection and use of plant material of the species. The frequencies were recorded weekly from January 2015 to December 2019. Phenological activity showed differences between accesses. The Spearman correlation index showed a direct and significant correlation only in fruiting in relation to temperature. The phenological record showed the maximum concentration of groups of accessions that had the highest average flowering days in August, September and October, especially in August. Fruiting recorded the highest average percentage of fruiting days in August, September, October and November, especially in October. It is suggested the collection of plant material of interest to the species from December to July, whose registration of the number of days that occur the phenophases undergoes reductions. It is pertinent to carry out further studies on the correlation of phenology with climatic events considering the performance of each access individually.